Pollution status and mercury sedimentation in small river near amalgamation and cyanidation units of Talawaan-Tatelu gold mining, North Sulawesi - T M Palapa; A A Maramis (Brawijaya University, 2015)
The activities of traditional gold mining in the region of Talawaan-Tatelu, North Minahasa regency, North Sulawesi, have been ongoing since 1998. Processing the gold in the mine consists of three stages i.e., the excavation, milling and amalgamation, and the use of cyanide tanks. Waste from the processing units which contains high mercury, generally flows directly into small rivers nearby. This study aimed to determine the pollution status and mercury sedimentation in a small river near the amalgamation and cyanidation processing units in Talawaan-Tatelu gold mining. Water and sediment samples were taken from seven stations along a small river, as many as four temporal replications (weekly). Mercury determination in water and sediments was done by using Cold Vapor Atomic Fluorescence Spectrometry. Pollution status was determined through the calculation of Hg ratio in water samples and in water quality criterion (4th class, as noted in The Indonesian Government Regulation No. 82 of 2001 on Water Quality and Water Pollution Control), while the mercury sedimentation was calculated from the ratio of mercury in water and sediment. The results showed that there are differences in the status of pollution and mercury sedimentation of seven sampling stations. Amalgamation and cyanidation processing units provide significant impact on the status of pollution (although it is categorized in contamination) and mercury sedimentation along small river in the gold mining area of Talawaan-Tatelu. The downstream of this small river, Talawaan River, is the main river of the Talawaan watershed. Things that should be a concern are Talawaan rural communities living near Talawaan River who often use the water for daily needs such as bathing and washing. Risk to public health around the river can arise when the status of pollution and mercury sedimentation are influenced by the amalgamation and cyanidation processing units.